Multi-market competition, R&D, and welfare in oligopoly - Akio Kawasaki; Ming Hsin Lin; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2010)
We investigate a multi-market Cournot model with strategic process R&D investments wherein a multi-market monopolist meets entrants that enter one of the markets. We find that entry can enhance the total R&D expenditure of the incumbent firm. That is, entry can stimulate R&D effort. Moreover, the incumbent's profit nonmonotonically changes as the number of entrants increases. Depending on the fixed entry costs and R&D technologies, both insufficient and excess entry can appear.
Keywords: L13; O32; L11; 330; multi-market; oligopoly; process R&D; entry; welfare; Markteintritt; Investition; Technischer Fortschritt; Wohlfahrtsanalyse; Oligopol; Theorie